(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This experimental work along with an analyticalanalysis is investigated.The behavior of simply supported steel beams with lightweight and normal concrete slab that have the same compressive strengthand slump was studied. Eight specimens tested under mid-point load and analysis by plastic analysis theory. Four of composite beams havea steel I-section beam with normal concreteslab and the other four with lightweight concrete slab. Different degrees of shear interaction were considered (100% to 40%). It was observed that there are no essential differences between the modes of failure that appeared in the tested composite beams with normal and lightweight concrete. Also, it was notedthat there is a decrease in the initial stiffness and also in the ultimate strength of the composite beams when the concrete of the flanges for the tested specimens was replaced from normal to lightweight concrete for different degrees of shear connections.The analytical results for all tested beam specimens, except that with normal concrete and 100% degree of shear interaction, gave overestimate results compared with those of experimental results.